PHYSIOLOGICAL STUDIES ON BACILLUS SPECIES ISOLATED EROM FERMENTED AFRICAN LOCUST BEAN [PARKIA BIGLOBOSA (JACQ.) BENTH-] (1988)
The physiological activities of Bacillus species that ferment African locust bean (Parkia biqlobosa (Jacq.) Benth] to produce ‘iru’ were investigated. The strains studied belong to the B. subtillis group and were designated BS1, BS2, BS3, BLl, BL2, BL4 and BP2. These seven strains showed significant differences (at α= 0.05) in growth and extracellular proteinases production. The following (descending) order was obtained for the growth of the organisms in liquid medium: BS3 > BS1 > BL4 > BL2 > BS2 > BL1 > BP2 The order of proteolytic activity (in descending Order) of the strains in nutrient broth medium containing African locust beans was: BL2 > BP2 > BS2 > BL4 > BS3 > BL1 > BS1 The best three strains (oh the basis of proteinase production) BL2, BP2 and BS2 showed further Variation in the production of other extracellular enzymes. The three strains produced amylase and polygalacturonase constitutively and varied amounts of sucrase and galactanase. Phytase activity was not detected in culture broth of strain BS2. None of the strains BS2, BL2 and BP2 produced pectinmethylesterase in nutrient broth medium with or without African locust bean. The three strains were lipolytic on tributyrate agar plates and produced trace amounts of lipase in broth medium containing African locust bean. In most cases, presence of African locust bean in culture medium enhanced production of extracellular enzymes significantly in the three strains. Agitation was found to be necessary for optimal production of extracellular proteinases by the strains BS2 and BL2. Among the carbon sources used, fructose and glucose repressed proteinase production significantly (at α = 0.05) in strain BS2 while raffinose and starch favoured proteinase production. Among the carbohydrates which favoured the production of proteinases are, inorder raffinose > starch > arabinose > galactose > sucrose. The effects of different nitrogen sources on proteinase production by strain BS2 were also investigated. Casein enchanced preduction but the effect was not significant (at α = 0.05) while other nitrogen sources repressed proteinase production significantly. The nitrogen sources repressed proteinase production in the Order: Leucine > Urea > KNO3 > NH4NO3 > Aspartic acid > Glutamic acid > Alanine. The presence of African locust bean in culture medium enhanced proteinase production in the three strains, but the effect was not significant (at α = 0.05). The crude proteinases of sttain BS2 had Optimum activity at pH 7.5. Optimum temperature for activity of the proteinases was 35°C, and the proteinases were relatively stable at 60°C, but were quickly denatured at temperatures > 70 C. The apparent Km of the crude proteinases of the strains BS2, BL2 and BP2 were approximately 39.14mg/ml, 33.29mg/ml and 44.1mg/ml respectively. Multiple proteinase bands were obtained after electrophoretic Separation of the crude enzymes in all strains. During purification, the proteinases were precipitated out between 55 - 70% of ammonium sulphate Saturation levels. There was a substantial loss in proteolytic activity during the salting out process. Three proteolytic activity peaks were obtained during ion-exchange chromatography of crude enzymes of strains BS2 and BL2. The peaks I, II and III were identified to be serine proteinase, neutral proteinase and an esterase (with low proteolytic activity) respectively. The serine proteinases of the two strains BS2 and BL2 showed hydrophobic properties. The molecular weights of the serine, neutral and esterase proteinases for strain BS2 were 29800, 24000 - 27400 and 33900 - 38400 respectively while those of strain BL2 were 18200 - 19700, 22600 and 33500 respectively. The purified neutral proteinase had higher specific activity than the serine proteinase while the esterase was characterized by low specific activity. The esterase was responsible for the multiple proteinase bands pattern observed in the electrophoresed crude enzymes. The possibility of selecting strains capable of producing wider variety and higher yields of extracellular enzymes to bring about more digestible fermented product is discussed.